Cognitive function in middle-aged and older adults participating in synchronized swimming-exercise - Tomokane, Sayaka; Okumura, Yuka; Ikeshima, Akiko; Tatsumi, Juri; Maeshima, Etsuko (Journal of Physical Therapy Science, 2017)
[Purpose] The purpose of the present study was to examine cognitive function in middle-aged and older adults regularly engaging in synchronized swimming-exercise. [Subjects and Methods] Twenty-three female synchronized swimmers ranging in age from 49 to 85 years were recruited for the present study. The duration of synchronized swimming experience ranged from 1 to 39 years. The control group consisted of 36 age- and gender-matched community-dwelling middle-aged and older adults (age range: 49 to 77 years). Cognitive function was evaluated using the Japanese version of the Montreal Cognitive Assessment (MoCA-J) and compared between the synchronized swimmers and control participants. [Results] No significant differences in mean total MoCA-J scores were observed between the synchronized swimmers and control participants (23.2 ± 3.1 and 22.2 ± 3.6, respectively). Twenty-nine subjects in the control group and 17 in the synchronized swimming group scored below 26 on the MoCA-J, indicative of mild cognitive impairment. Significant differences in delayed recall—but not in visuospatial/executive function, naming, attention, language, abstraction, or orientation—were also observed between the two groups. [Conclusion] The results of the present study suggest that synchronized swimming has beneficial effects on cognitive function, particularly with regard to recent memory.